The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-91121-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of re-excimer laser phototherapeutic keratectomy (re-PTK)

Abstract: To assess the surgical outcomes of re-excimer laser phototherapeutic keratectomy (re-PTK) for recurrent disease after initial PTK. Retrospective cohort study with historical comparison group. This study involved 56 patients who underwent re-PTK (mean follow-up period: 47.9 ± 36.2 months) at the Baptist Eye Institute, Kyoto, Japan. In all subjects, corrected-distance visual acuity (CDVA) before and after re-PTK was compared. Postoperative recurrence of corneal lesion with a decrease of CDVA of two lines or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…15 A study by Hieda et al reported no significant differences in recurrence rates between first PTK treatment and repeated PTK in patients with variant types of corneal dystrophy. 16 There are no studies on the recurrence interval after PTK + EP in corneal dystrophy; in this case, however, RBCD recurred 4 years after the first PTK and again 5.5 years after the PTK + EP procedure, suggesting that PTK + EP exhibits a recurrence time comparable with that of PTK and is effective in delaying the need for corneal transplantation. In addition, Olson et al and Caldwell et al reported 2 cases of RBCD recurring in the graft 10 years after undergoing penetrating corneal transplantation, and Salouti et al concluded that prior PTK is a risk factor of corneal dystrophy recurrence after corneal transplantation.…”
Section: Discussionmentioning
confidence: 71%
“…15 A study by Hieda et al reported no significant differences in recurrence rates between first PTK treatment and repeated PTK in patients with variant types of corneal dystrophy. 16 There are no studies on the recurrence interval after PTK + EP in corneal dystrophy; in this case, however, RBCD recurred 4 years after the first PTK and again 5.5 years after the PTK + EP procedure, suggesting that PTK + EP exhibits a recurrence time comparable with that of PTK and is effective in delaying the need for corneal transplantation. In addition, Olson et al and Caldwell et al reported 2 cases of RBCD recurring in the graft 10 years after undergoing penetrating corneal transplantation, and Salouti et al concluded that prior PTK is a risk factor of corneal dystrophy recurrence after corneal transplantation.…”
Section: Discussionmentioning
confidence: 71%